Ceramic Matrix Based on Red Clay Functionalized with Fe₂O₃ for Arsenic Adsorption - Trejo Espinoza, Abrahán Fernando (2025)
Arsenic contamination in water represents a serious public health issue worldwide, particularly in regions where natural or anthropogenic sources contribute to concentrations exceeding the maximum permissible limit of 0.01 mg/L established by the World Health Organization. This study evaluated the efficiency of a ceramic matrix made from red clay impregnated with ferric oxide (Fe₂O₃) for arsenic removal and water quality improvement. Water samples were collected from the Apacheta River and treated using a continuous-flow system with supports calcined at 800 °C. Arsenic concentrations were determined by spectrophotometry, and physicochemical parameters were analyzed before and after treatment. The results showed a reduction in arsenic concentration from 0.17 mg/L to 0.0053 mg/L, achieving a removal efficiency of 94.5 %, along with improvements in turbidity, electrical conductivity, and dissolved solids. Statistical analysis revealed significant differences (p < 0.05) in all evaluated parameters. In conclusion, the proposed ceramic matrix represents a viable and sustainable technological alternative for the purification of natural waters contaminated with arsenic, applicable in various regions affected by this pollutant.